(untitled) (Research, Society and Development, 2025)
Mammary tumors in bitches are one of the most common neoplasms in this species and are influenced by hormonal and environmental factors. The aim of this study was to analyze the clinical, diagnostic and therapeutic aspects of mammary tumors in female dogs. The methodology used consisted of researching scientific articles in databases such as Google Scholar, PubMed and Scielo, using terms linked to mammary tumors, neoplasms and dogs. The findings suggest that the disease usually manifests itself in elderly dogs, with the most frequent presence of mammary nodules, with malignant potential in more than 50% of cases. Diagnosis is based on clinical, cytological and histopathological analyses to establish the nature of the tumor and its prognosis. Therapy involves the surgical removal of the tumor, which may involve total or partial mastectomy, whether or not associated with complementary therapies such as chemotherapy. Early castration is seen as an effective prevention strategy. Even with the seriousness of malignant cases, the prognosis can be promising, as long as diagnosis and treatment are early. It is essential that owners pay attention to clinical signs and maintain regular veterinary follow-up. This study concludes that proper management and early treatment can significantly improve the quality of life of affected bitches.